Cranial anatomy of Microsyops annectens (Microsyopidae, Euarchonta, Mammalia) from the middle Eocene of Northwestern Wyoming. (September 2020) - Silcox, Mary T.; Gunnell, Gregg F.; Bloch, Jonathan I.
Abstract: The Microsyopidae are extinct mammals from the late Paleocene–late Eocene of North America and the late Paleocene of Europe. While results from phylogenetic analyses support euarchontan affinities, specific relationships of microsyopids to other plesiadapiforms (plausible stem primates), Euprimates (crown primates), Scandentia (treeshrews), and Dermoptera (colugos) are unresolved. An exceptionally well-preserved cranium of Microsyops annectens includes a basicranium that is generally primitive relative to that of other extinct and extant euarchontans in having: (1) a transpromontorial groove for an unreduced internal carotid artery (ICA) entering the middle ear posteromedially; (2) grooves (not tubes) on the promontorium, marking the course for both stapedial and promontorial branches of the ICA; (3) a foramen faciale that opens into the middle ear cavity, with the facial nerve exiting through a stylomastoid foramen primitivum; and (4) unexpanded caudal and rostral tympanic processes of the petrosal. The absence of any preserved bullar elements in the middle ear contrasts with that of other plesiadapiforms for which the region has been recovered, all of which have evidence of an ossified bulla. Microsyops lacks many of the specialized cranial characteristics of crown scandentians and dermopterans. The basicranial anatomy of microsyopids does not provide evidence in support of a clear link to any of the extant euarchontans, and suggests that the primitive morphology of this region in Euarchonta was little differentiated from that observed in the primitive placental mammals.